PSYCHOPOETRY THERAPY MODEL TOWARDS ENHANCING COGNITIVE'S INSIGHT CLIENTS ON MENTAL DISORDERS IN PSYCHIATRIC HOSPITAL - Yeni Hendriani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Cognitive's insight is an important aspect in determining the diagnosis and treatment programs to clients with mental disorders. Psychopoetry therapy as an intervention modality based on the reading and writing of poetry those are expressive of the feelings of the client. Purpose of this study was to determine the effect of therapy models psychopoetry to measure themselves in the improvement of cognitive (self-assurance component) on the client's mental disorder. Benefits psychopoetry therapy as a means of expressing feeling depressed clients and are thought to contribute to the problem at hand. Method. The research method was used quasi-experimental research design with non-randomized pretest-posttest control group. Result. The results of this research were significant changes in the intervention group before and after treatment, and when compared with the control group (p < 0.05). Discussion. Psychopoetry therapy model can be used in addition to other therapeutic nursing interventions that have been implemented. This model is able to optimize the ability to build the structure of phrase in communication and recommended the development of writing skills productively. Keywords: Psychopoetry therapy, insight, cognitive, modification, expressive